Augusto Abelaira e Osman Lins: leitura, intertextualidade, metaficção e romance-diário - Camargos, Kellen Millene (2013)
During the 20th century, more specifically second half, the romance authors resumed and accentuated reflections upon the novel construction. The look for the writing of literary text has resulted in a more direct interaction with the reader and has demanded a coparticipation in the meaning-making of the text, because the metafictional, along side other narrative strategies, instead of making the reading easier, has problematized it. The novel narcissistic look has accentuated, too, the reflection on many aspects, such as: the intertextuality and the assimilation of other discursive genres. In this sense, this work has aimed the study of these referred aspects in two novels from authors that belonged to the same period, but in different countries and that used, practically, the same aesthetic resources: Bolor (1999), from the Portuguese writer Augusto Abelaira, published in 1968, and A rainha dos cárceres da Grécia (1979), from the Brazilian writer Osman Lins, published in 1979. Thus, the present study is justified for both of the novels have, in their composition, very similar narrative strategies: explicit intertextuality with universal literature works from different periods, metafictionality and the use of the diary novel form. Other aspects are correlated to these ones, as the fusion of time and space, similar themes in both works, voice plurality, amongst others. This work’s aim is based on the assumption that the studies of the referred aspects, having as a starting point the intertextual relations in the novels of Abelaira and Lins with the work that they quote, is constituted in a reading key to the meaning-making in each one of these novels. To accomplish this comparative study, theories that base the composition aspects of these novels were used. Regarding intertextuality, Mikhail Bakhtin’s (1981), Julia Kristeva’s (1974), Laurent Jenny’s (1979) e Gerard Genette’s (2006) theories were used. The argumentation around the metafiction idea is sustained, specially, in critical texts about both novels. To study the diary novel issue, Valérie Raoul’s (1999), Béatrice Didier’s (1976), Sheila Dias Maciel’s (2012), Maria Luiza Ritzel Remédios’ (1997) theories were used, amongst others. To accomplish the study of such aspects, based on the intertextuality, work quoted on both novels were read. All of the quoted texts in Bolor were analyzed, but the book Dias íntimos, for it was sold out at the bookstores. Among the quoted texts in A rainha dos cárceres da Grécia, seven works, that have some relation to the strategies studied, were analyzed. We conclude that the narrative strategies that are the structure of both main novels require a participant reader whom may read carefully the diary fragments and make its meanings, taking into account that some of them can only be perceived in the relation of those main novels with the work that they quote.